Sintesis Bio-nanosurfaktan sebagai Deterjen Ramah Lingkungan dari Kombinasi Ekstrak Getah Pepaya (Carica papaya L) dan Daun Sengon (Paraserianthes falcataria L. Nielsen) - Tunjung Wahyu Widayati; Hendri Yudisai; I K Gary Devara (Seminar Nasional Teknik Kimia Kejuangan, 2018)
The purpose of this research is to study formulations Bio-Nano Surfactant by combining papaya sap, Sengon leaf, and HCl to obtain the most efficient concentration in neutralizing calcium oxalate, determine the effect of detergency by Bio-Nano Surfactant and determine the level of contamination by Bio-Nano Surfactant